Diet and Genotype Effects on n-3 Polyunsaturated Fatty Acids of Beef Lipids - Garcia, Pilar Teresa (2017)
The aim of this study was to study the effects of four feeding systems on n-3 Polyunsaturated Fatty Acids (PUFAs) in Longissimus dorsi muscle lipids from three different steer genotypes and discuss the current finding concerning the role of these factors on alfa-linolenic acid conversion into n-3 long chain PUFAs. The feeding systems described here, represent productive models widespread in Argentina Pampeana region, ranging from pasture exclusive diet, to the feedlot system. C18:2 n-6 (LA) increased whereas C18:3 n-3 (ALA) decreased according to the increase in grain in the diet. The LA/ALA and n-6/n-3 PUFAs ratios increased as the grain in the diet increased. We concluded that by feeding animals correctly, we address the problem of consuming a high n-6/n-3 PUFAs ratio without virtually changing normal diets. Although these changes appear modest, for non-sea fish eaters, animal products such as beef are the only sources of long-chain n-3 PUFAs, and any improvement in the fatty acid composition of beef will result in an increase in the consumption of n-3 fatty acids.